Arduino-Based Baby Bath System with Accurate Water Level and Temperature Control - Prasetyo, Arya Aji; Kurniawan, Edy; Johari, Norhasnidawani; Arifin, Rizal (JURNAL NASIONAL TEKNIK ELEKTRO, 2025)
Infant bathing can be challenging for parents due to safety and temperature control concerns. This study aimed to develop and evaluate a fully automated baby bathtub system featuring water level and temperature control using an Arduino Mega 2560 microcontroller. This system was designed to ensure a safe and comfortable bathing environment for infants while providing convenience for parents. The methodology involved designing and assembling key components, including a 4x4 keypad, relays, water level, and temperature sensors. The system underwent comprehensive testing to evaluate its functionality and accuracy. The results showed that the system maintained a consistent water level of 9 liters and controlled water temperature within a narrow range. For example, when the actual water temperature was 37.8°C, the sensor reading was 37.5°C, demonstrating a minor deviation of 0.3°C. Overall, temperature deviations ranged from 0.5°C to 1.0°C from the setpoint. The total operation time for preparing the bathtub, including heating and filling, ranged from 15 to 20 minutes. All components functioned correctly during testing, confirming the system's reliability and accuracy. In summary, the automated baby bathtub system successfully meets its design objectives, offering a safe, efficient, and user-friendly solution for infant bathing while assuring parents of its safety and ease of use.